The Role of Transformational Leadership and Motivation on Employee Performance - Sumarsi, Sumarsi (Journal of Industrial Engineering & Management Research, 2019)
This study aims to see the effect of transformational leadership and work motivation on employee performance. The method used in this study is a quantitative verification method. The instrument used is a questionnaire consisting of 30 statements given to 290 employees. Sampling was done by accidental technique (convenient sampling). The research data were analyzed using Smart PLS version 3.0. The results showed that transformational leadership had a significant effect on employee performance (p<0.05), work motivation had no significant effect on employee performance (p>0.05), and transformational leadership mediated by motivation had no significant effect on employee performance (p >0.05). Further research is expected to create a transformational leadership improvement model that can increase employee motivation and performance.